Effects of Algan hemostatic agent foam in rat femoral artery injury model: A randomized animal trial : Algan hemostatic agent act on artery injury model - Şener, Dila; Aydın, Atakan; Cücü, Ekin; Adademir, Taylan; Türet, Deniz Mukaddes; Karadağ, Mehmet (Journal of Surgery and Medicine, 2022)
Background/Aim: Nowadays, many deaths are related to vessel injury-induced blood loss. Failure to control bleeding also increases the risk of death. This study aimed to investigate the hemostatic effects of the Algan Hemostatic Agent (AHA) foam application in a rat model in which severe femoral artery bleeding was induced. Methods: Fourteen rats were randomly assigned to two groups: (1) control (physiological saline) (n = 7) and (2) AHA foam (n = 7). The left femoral artery of the rats was incised and when the bleeding started, and the area was pressed with another sponge for 10 s in all rats. Afterwards, physiological saline solution impregnated gauze or AHA foam was placed over same area. A chronometer was started and area was checked after 2 min. If no bleeding occurred during the first 2 min of application, it was recorded as “successful”. If bleeding occurred, the same procedure was repeated up to three times. If hemostasis could not be achieved even after the third application, it was considered a failure, and “failed” was recorded. All animals were sacrificed under high anesthesia for least 10 min after the experiment. Results: Application of AHA resulted in complete (100%) control of bleeding in all rats within the first 2 min. In control group, hemostasis was achieved in 1 out of 7 (14.3%) rats by the third application. Failure was recorded for the remaining six rats. The hemostatic success rate of the AHA foam was significantly higher than the rates of control group (P = 0.005). Conclusion: AHA foam is a very effective hemostatic agent and can be applied easily on vascular trauma models. Further studies are needed to elucidate hemostatic features of AHA.